Pairing Islamic Teachings And Communism: Misbach's Hajj Thoughts (1912-1926) - Kuswono Kuswono; Ketut Adi Saputra; Ragil Agustono (Criksetra: Jurnal Pendidikan Sejarah, 2019)
The purpose of this study is to describe Haji Misbach's thoughts on Islam and Communism in 1912-1926. Research methods use historical research by analysing sources related to Misbach's thinking. Misbach who juxtaposed between Communism and Islamic teachings had an impact on the emergence of the anti-capitalist movement, various widespread support to fight capitalism, and the independence of the bumiputra people. Haji Misbach made a new thing by raising propaganda through the mass media of Islamic Communism. Islam with Communism has some similarities, one of which is that both are very opposed to oppression and both also fight for freedom. On that basis, Hajj Misbach has the spirit of struggle for the privilege of human rights of workers based on Islam and with the tools of Communism to fight Dutch capitalism.